Is transanal irrigation the best treatment possibility for low anterior resection syndrome? A multicenter, randomized clinical trial: study protocol - Klimovskij, Michail; Civilka, Ignas; Aleinikov, Andrej; Aukstikalnis, Tomas; Christensen, Peter; Dulskas, Audrius (Frontiers in Surgery, 2024)
Background: Up to 50% of patients who undergo rectal resection suffer from various and partly severe functional problems, despite the preservation of the anal sphincter. These complaints are defined as low anterior resection syndrome (LARS). So far, there are no randomized clinical trials regarding the most effective treatment for LARS. Our aim is to evaluate whether transanal irrigation improves bowel function and quality of life in patients following low anterior resection compared to best supportive care.Methods: Patients who have undergone low anterior resection will be approached for this study. On patient's visit, complaints regarding the defecation, as well as any deterioration in their overall quality of life will be assessed using questionnaires such as the Low anterior resection syndromes score, Wexner score, EORTC QOL CR-29 and Measure Yourself Medical Outcome Profile tool. Few additional target questions will be also asked, as "Would you recommend the treatment to anybody; did you expect the improvement following the treatment; etc". Questionnaires and scales will be filled on follow up visits every 3 months for 1 year.Discussion: This multicentre, randomized controlled trial will lead to better understanding of LARS treatment. Moreover, it will be hypothesis generating and inform areas needing future prospective studies.